PERCEPTIONS ON USING MOBILE PHONE IN LEARNING ENGLISH BY THE THIRD YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP, UNIVERSITAS RIAU - Annysa Wahyu Ningsih; Supriusman Supriusman; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to know and describe the students’ perceptions on using mobilephone in learning English. The population of the research is the third-year students ofEnglish study program of FKIP, Universitas Riau. The number of the sample is 76 studentsfrom class IIIB and IIIC class. The collected data was used by an online questionnaire fromGoogle Form and shared via WhatsApp. The research was analyzed by using SPPS Ver 24and Microsoft Excel to know the percentage. Based on the result, there are four indicators.First, Students’ Perception on Intension to use mobile phone in learning English whichstudents would like to practice other English skills using mobile phone (48.6%). The second,students’ perception of engagement in mobile phone to support learning English activitieswhich students mostly use Google apps to brows material English (51.3%). Then, students’perceptions about benefits of mobile phone to support learning English which mobile phoneis a highly practical and flexible as a learning media. The last, students’ perceptions aboutobstacles of mobile phone to support learning English which they feel frustrated using mobilephone because of the slow internet network (59.2%). This study implies that the third-yearstudents of English study program of FKIP, Universitas Riau have a good perception onusing mobile phone in learning English.Key Words: Perception, Mobile Phone, Learning, English